2016
DOI: 10.3390/sym8020007
|View full text |Cite
|
Sign up to set email alerts
|

On the Boundedness and Symmetry Properties of the Fractal Sets Generated from Alternated Complex Map

Abstract: A complex map can give rise to two kinds of fractal sets: the Julia sets and the parameters sets (or the connectivity loci) which represent different connectivity properties of the corresponding Julia sets. In the significative results of (Int. J. Bifurc. Chaos, 2009Chaos, , 19:2123Chaos, -2129 and (Nonlinear. Dyn. 2013, 73:1155-1163, the authors presented the two kinds of fractal sets of a class of alternated complex map and left some visually observations to be proved about the boundedness and symmetry pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To further reveal the complex internal structure of the M-J set, some supplementary studies, including quantitative methods and visualization methods, were proposed and added to ETA [28][29][30][31][32][33][34][35]. For instance, by analyzing the trajectory of the critical points, Danca et al [28,29] pointed out that the Julia set showed different connectivity by alternating the iteration of switched systems [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further reveal the complex internal structure of the M-J set, some supplementary studies, including quantitative methods and visualization methods, were proposed and added to ETA [28][29][30][31][32][33][34][35]. For instance, by analyzing the trajectory of the critical points, Danca et al [28,29] pointed out that the Julia set showed different connectivity by alternating the iteration of switched systems [30].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by analyzing the trajectory of the critical points, Danca et al [28,29] pointed out that the Julia set showed different connectivity by alternating the iteration of switched systems [30]. Afterwards, a kind of fractals paradox phenomenon "disconnected+disconnected=connected" and the corresponding graphical investigations were proposed in [31,32]. The Julia deviation distance method and Julia deviation plot method were given in the study of noise-perturbed Julia sets [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies on fractals analyzed the symmetry property of the planar M-set generated from map (1) [2] and some generalized maps [19]. Recently, scholars have focused their attention on the symmetry property of the spatial M-set [11,20]. In [20], the authors proved the symmetry of the 3D slice of the M-set generated by an alternative map.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scholars have focused their attention on the symmetry property of the spatial M-set [11,20]. In [20], the authors proved the symmetry of the 3D slice of the M-set generated by an alternative map.…”
Section: Introductionmentioning
confidence: 99%